Optical imaging with subnanometric vertical resolution using nanoparticle-based plasmonic probes - Scarpettini, Alberto Franco (2009)
We present images with subnanometric optical resolution using novel metal nanoparticle-based probes in a Field Enhancement Scanning Optical Microscope. The probe is built of silica microspheres decorated with silver nanoparticles, which act as enhancers of the optical field. The optical resolution is dependent on the wavelength and polarization of the exciting field, and the approach curves reveal the enhancement due to cavity modes between the plasmonic probe and the sample. © 2008 Elsevier B.V. All rights reserved.